Divagazioni romane. Al caffè con ROBOCOOP (RomaBolognaCooperazione) (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2021)
The experience of ROBOCOOP, RomaBolognaCooperazione is commented by the authors of this testimony to try to identify the cultural roots of the collective’s activity, university training and the future possibilities of their experimentation.